The war of words : a glossary of globalization - James, Harold, 1956- (Yale University Press, 2021)
Nationalism, conservatism, liberalism, socialism, and capitalism are among the most fiercely debated ideas in contemporary politics. Since these concepts hark back to the nineteenth century, much of their nuanced meaning has been lost, and the words are most often used as epithets that short-circuit productive discussion. In this insightful book, Harold James uncovers the origins of these concepts and examines how the problematic definition and meaning of each term has become an obstacle to respectful communication.0 Noting that similar linguistic misunderstandings accompany such newer ideas as geopolitics, neoliberalism, technocracy, and globalism, James argues that a rich historical knowledge of the vocabulary surrounding globalization, politics, and economics-particularly the meaning and the usefulness that drove the original conceptions of the terms-is needed to negotiate the gaps between different understandings and make fruitful political debate once again possible.